2017
DOI: 10.1007/s10096-017-2990-z
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory viral infections are underdiagnosed in patients with suspected sepsis

Abstract: The study aim was to investigate the prevalence and clinical relevance of viral findings by multiplex PCR from the nasopharynx of clinically septic patients during a winter season. During 11 weeks of the influenza epidemic period in January–March 2012, consecutive adult patients suspected to be septic (n = 432) were analyzed with cultures from blood and nasopharynx plus multiplex PCR for respiratory viruses on the nasopharyngeal specimen. The results were compared with those from microbiology analyses ordered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…We observed that viral sepsis was not a risk factor for in-hospital mortality in patients without septic shock. Our data support those of previous studies in which respiratory viruses were frequently found in critically ill patients with pneumonia but mortality rates did not significantly differ between patients with bacterial infection and those with viral infection [9,10,14]. This highlights the need to identify patients at higher risk of viral sepsis and the importance of a complete microbiological diagnosis in cases of CAP.…”
Section: Mortalitysupporting
confidence: 89%
See 2 more Smart Citations
“…We observed that viral sepsis was not a risk factor for in-hospital mortality in patients without septic shock. Our data support those of previous studies in which respiratory viruses were frequently found in critically ill patients with pneumonia but mortality rates did not significantly differ between patients with bacterial infection and those with viral infection [9,10,14]. This highlights the need to identify patients at higher risk of viral sepsis and the importance of a complete microbiological diagnosis in cases of CAP.…”
Section: Mortalitysupporting
confidence: 89%
“…No statistically significant difference was observed between the two groups in terms of in-hospital mortality, ICU mortality, length of ICU stay, 30-day mortality, and 1-year mortality (Table 1). However, patients with sepsis showed longer length of hospital stay, were more frequently admitted to ICU and needed (10) .032 more frequently invasive mechanical ventilation than patients without sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 432 non-transplant patients with suspected sepsis in the previous study, 12 (2.8%) had RSV A/B and 23 (5.3%) had hMPV. 33 Gréve et al reported 7 (0.5%) with hMPV and 21 (1.5%) with RSV among 1407 non-transplant patients admitted to the ICU on MV therapy in a prospective multicenter study in 2018. 11 Recent reports support our findings and indicate that hMPV and RSV should not be regarded as negligible pathogens and could be under-diagnosed in non-transplant critically ill patients, in particular on ventilated and ICU care.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to diagnose co-infections is a significant improvement as these can be associated with increased morbidity and mortality (Burk et al, 2016;Marcos et al, 2009;Rea-Neto et al, 2008). Rapid molecular tests have been shown to reduce the length of hospital stay and the cost of testing for those with viral respiratory testing and has facilitated a more targeted approach to patients presenting with respiratory infections with respect to treatment regimens, need for admission and infection control concerns (Barenfanger et al, 2000;Ljungström et al, 2017;Pavia, 2011;Woo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%